KEBIJAKAN HUKUM PIDANA DALAM PENYELESAIAN TINDAK PIDANA PENGEBORAN MINYAK TANPA IZIN (ILLEGAL DRILLING) DI KABUPATEN MUSI BANYUASIN - Indah Purnama Dewi; Maria Silvya Elisabeth Wangga (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
The thesis aims to assess criminal law policies in the completion of unlicensed drilling of oil in musi banyuasin district which is a growing problem in the region, which not only affects economic and environmental damage, but also creates a major challenge to law enforcement. The problem raised is a criminal law policy in settling illegal oil drilling crimes in musi banyuasin district in ruling number: 225/ Pid. B/2020/PN Pkb; Rule number: 295/ Pid. SUS /2020/PN Bgl; Rule number: 326/Pid.B/LH/2024/PN Plg according to migas and non-panel policy against illegal oil drilling charges in musi district in the future. The study uses normalizing juridical juridical approaches and collects data in qualitative ways that discuss current law laws, law enforcement practices, and the challenges facin solving illegal cases. The main focus of the study is criminal law policies adopted by law enforcement officials and suggested more optimal measures to prevent and address these crimes. Studies have shown that while regulations governing illegal activity, the implementation of the law in the field still faces serious obstacles, in terms of coordination between institutions, human resources, and the legal consciousness of society. Hence, the study requires increased capacity on law enforcement officers, improved cooperation between related agencies, and public education to implement non-penal policies on unauthorized drilling of oil in musi banyuasin counties. Keywords: Illegal Drilling, Non Penal, Musi Banyuasin.